2016
DOI: 10.7554/elife.18972
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of encapsulated ferritin provides insight into iron storage in bacterial nanocompartments

Abstract: Ferritins are ubiquitous proteins that oxidise and store iron within a protein shell to protect cells from oxidative damage. We have characterized the structure and function of a new member of the ferritin superfamily that is sequestered within an encapsulin capsid. We show that this encapsulated ferritin (EncFtn) has two main alpha helices, which assemble in a metal dependent manner to form a ferroxidase center at a dimer interface. EncFtn adopts an open decameric structure that is topologically distinct from… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
149
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(161 citation statements)
references
References 49 publications
12
149
0
Order By: Relevance
“…In vivo protein encapsulation is guided by short targeting peptides (TPs), which are located at the C-termini of cargo proteins. A large variety of native cargo proteins has been identified in bacteria and archaea, including peroxidases and ferritin-like proteins involved in stress response pathways 11,[14][15][16] . Using Escherichia coli as a host, it has been shown that packaging of non-native proteins into the encapsulins from Thermotoga maritima and Brevibacterium linens can be achieved by fusion of targeting peptides to the intended cargo 17,18 .…”
Section: Introductionmentioning
confidence: 99%
“…In vivo protein encapsulation is guided by short targeting peptides (TPs), which are located at the C-termini of cargo proteins. A large variety of native cargo proteins has been identified in bacteria and archaea, including peroxidases and ferritin-like proteins involved in stress response pathways 11,[14][15][16] . Using Escherichia coli as a host, it has been shown that packaging of non-native proteins into the encapsulins from Thermotoga maritima and Brevibacterium linens can be achieved by fusion of targeting peptides to the intended cargo 17,18 .…”
Section: Introductionmentioning
confidence: 99%
“…The encapsulated ferritins ( EncFtn ) are recently described members of the ferritin superfamily (13). These proteins are sequestered within encapsulin nanocompartments, and the two proteins act in concert to provide an iron storage system with a much greater capacity than the classical ferritins and DNA-binding Protein from Starved cells (DPS) nanocages (3, 4).…”
mentioning
confidence: 99%
“…A newly discovered class of protein organelles called encapsulin nanocompartments are implicated in microbial iron and redox metabolism and have so far only been shown to be involved in oxidative stress response (10)(11)(12)(13). Previously reported encapsulins share an HK97 phage-like fold and self-assemble from a single capsid protein into icosahedral compartments between 24 and 32 nm in diameter with triangulation numbers of T = 1 (60 subunits) and T = 3 (180 subunits), respectively (11,12,14).…”
mentioning
confidence: 99%